Rancangan Unit Pengelola Irigasi Modern di Indonesia - Bastin Yungga Angguniko; Susi Hidayah (Balai Teknik Irigasi, 2017)
Establishment of irrigation management unit in Indonesia has been addressed by the 2015-2019 National Five Year Plan. The need is based upon the weak management of irrigation networks. Out of 3.3 million hectare of irrigation networks, 52% is in poor condition in 2014. Therefore, development of irrigation unit led by a single managing unit is considered as an appropriate measure for improvement. This research tries to determine the essential factors in creating a modern irrigation management unit (UPIM). The effort is carried out through the auditing of the current irrigation management practices within the central irrigation schemes, either under self-management or through support assignment. Result from field survey is then analyzed using SWOT method, followed by determining the key success factors for the management. There are five main functions of modern irrigation management which are; (1) programming and information system, (2) operation and maintenance controlling, (3) irrigation protection, (4) knowledge center and human resources, and (5) water use planning and counseling (PTGA). Both knowledge center and PTGA are the managerial innovation of this research. All of the functions are then arranged as an organizational structure designed according to each irrigation typology. For the sake of successful UPIM implementation, support in the form of legal decree as well as operation manual that could be easily understood by all stakeholders are needed.